LISTENING COMPREHENSION PROBLEMS AMONG EFL VOCATIONAL SCHOOL STUDENTS - Nurhandayani S.; Eliza Nur Fadila; Zuhad Ahmad (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2020)
Listening to a conversation, dialogue, or a story in foreign language is an activity which needs effort to understand the content. There are several aspects that should be considered to do accordingly. This research investigated the main problems of listening comprehension in English as a foreign language faced by vocational high school students. Thirty students of the first grade participated in the research. The quantitative descriptive and qualitative methodologies were applied in this study with questionnaires and interviews used as instruments for collecting data. The findings show that the foremost problems of understanding the spoken text are the unfamiliar accents and topics. The other problems also have contribution to the students’ comprehension. They are noises, poor quality equipment, long spoken text, and the high speed of delivery. The findings of this study is expected to provide valuable information for English teachers regarding the listening difficulties faced by English as a foreign language students, which enable them to help students to improve their listening skills.